Successful treatment of vaginal malakoplakia in a young cat. Issue 2 (October 2016) - Cattin, Ryan P; Hardcastle, Michael R; Simpson, Kenneth W
Case summary: A 3-year-old, female, spayed, domestic shorthair cat presented for dysuria and haematuria, unresponsive to antibiotic treatment. A small, fleshy, erythematous mass protruded from the vaginal vault. Ultrasound identified a vaginal mass effect with mixed echogenicity measuring in excess of 3 cm. Vaginoscopy confirmed an extensive, fleshy, irregular mass that was characterised histologically as pyogranulomatous vaginitis, with periodic acid–Schiff-positive macrophages containing gram-negative bacteria. Fluorescence in situ hybridisation analysis demonstrated invasive intracellular Escherichia coli. Vaginal malakoplakia was diagnosed. Tissue culture and antimicrobial susceptibility of E coli was used to guide treatment. A 6 week course of enrofloxacin 5 mg/kg q24h resulted in complete resolution of the mass and clinical signs. Relevance and novel information: Malakoplakia is a rare chronic inflammatory condition that has been previously reported in the bladder of two cats. The pathogenesis of malakoplakia is thought to involve ineffective killing of bacteria (eg. E coli ), similar to granulomatous colitis in Boxers and French Bulldogs. The literature on malakoplakia in cats is sparse. This is the first reported feline case with vaginal involvement, intracellular E coli and successful treatment with a fluoroquinolone. Malakoplakia is an important, non-neoplastic differential diagnosis when a mass is identified in the urogenital system of a young cat.